Pengaruh Terapi Seni Menggambar Terhadap Harga Diri Warga Binaan Pemasyarakatan Di Rutan Kelas 2b Wonogiri - Makmur Sri Setyaningrum; Rufaida Nur Fitriana; Saelan Saelan (PENA NURSING, 2023)
The prisoners who were sentenced at prison, face a number problems that affecting their psychology. One of the problem is self-esteem. The objective of this research is to determine the effect of art therapy on self-esteem of the prisoners of Class 2B Jail, Wonogiri. This research used a quasy experimental design with nonequivalent control group design. Its population consisted of 235 drug convicts. The used sample was purposive sampling of 18 as control group and 18 as the treatment group. Data analysis in this research used paired t test because the ratio scale data were normally distributed. The result showed that self-esteem before doing art therapy in the control and treatment group was 10.44, self-esteem after doing art therapy in the control group was 11.89, while the treatment group had an 20.56.  There is an effect of art therapy on self-esteem of the prisoners of Class 2B Jail, Wonogiri